Design Thinking for Kami Peduli Website to Mobilize Community Disaster Response - Nanda, Rifqi; Anggun Pratama, Septiano; Pusadan, Mohammad Yazdi; Anshori, Yusuf (IAIC Transactions on Sustainable Digital Innovation (ITSDI), 2024)
Central Sulawesi, particularly Palu City, is a disaster-prone area with communities lacking sufficient knowledge and preparation for natural disaster risks. This study aims to develop a sustainable digital platform that enhances community preparedness through a user-friendly and engaging website design. By applying the Design Thinking method, the platform integrates sustainable digital innovation to provide essential information on disaster-prone areas, volunteer opportunities, and donation channels. The platform’s design prioritizes efficient use of digital resources to minimize environmental impact, supporting long-term resilience and community mobilization. Utilizing both qualitative and quantitative approaches, data was gathered through questionnaires and interviews with PMI staff, volunteers, and the public. The Design Thinking stages: Empathize, Define, Ideate, Prototype, and Test, were employed to create a responsive and effective user experience. SEQ testing results revealed an average usability score of 4.25, highlighting the platform's ease of use. This project contributes to sustainable innovation in disaster preparedness by leveraging digital resources to empower communities in Central Sulawesi.